2015
DOI: 10.4081/gh.2015.328
|View full text |Cite
|
Sign up to set email alerts
|

A review of spatial technologies with applications for malaria transmission modelling and control in Africa

Abstract: Spatial technologies, i.e. geographic information systems, remote sensing, and global positioning systems, offer an opportunity for rapid assessment of malaria endemic areas. These technologies coupled with prevalence/incidence data can provide reliable estimates of population at risk, predict disease distributions in areas that lack baseline data and provide guidance for intervention strategies, so that scarce resources can be allocated in a cost-effective manner. This review focuses on the spatial technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Generally, malaria incidence increases with warm and wet conditions, where higher temperature leads to increasing malaria incidence as it contributes to shortening extrinsic incubation period of Anopheles mosquito [8] [12]. Generally, it was suggested that the optimum temperature for Anopheles mosquito and parasite development ranges between 20˚C and 30˚C and they are subjected to thermal death if temperature rises above 40˚C or drops below 16˚C [13]. Yet, it is worth mentioning that the impact of temperature on malaria cannot be fully explained only by mean temperature [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, malaria incidence increases with warm and wet conditions, where higher temperature leads to increasing malaria incidence as it contributes to shortening extrinsic incubation period of Anopheles mosquito [8] [12]. Generally, it was suggested that the optimum temperature for Anopheles mosquito and parasite development ranges between 20˚C and 30˚C and they are subjected to thermal death if temperature rises above 40˚C or drops below 16˚C [13]. Yet, it is worth mentioning that the impact of temperature on malaria cannot be fully explained only by mean temperature [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mapping malaria has been promoted by increasing data availability, improved insight into environmental covariates of malaria risk, advances in analytical techniques [21] and availability of affordable Geographical Information Systems (GIS) software [4]. The application of GIS was not restricted only to mapping malaria incidence but extended also to include assessing the relationship between malaria and underlying factors, developing malaria early warning systems [13] and planning for malaria control programs [22]. This was motivated by the nature of data on malaria incidence and underlying climatic, topographic and socioeconomic factors are spatial variables that can be modeled and manipulated through GIS due the great capabilities of such systems in terms of handling and analyzing spatial data.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial technologies are providing unprecedented opportunities for rapid risk assessment in malaria-endemic areas [23] by overlaying ecological data relevant to mosquito breeding and transmission, notification data and access to health services. These technologies enable the development of decision support systems for more accurate and timely responses [24], including active case detection through cluster surveys and timely case follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, they developed and tested a model able to predict malaria evolution and thus, guide public health decisions. Applications of spatial technologies for malaria transmission modeling and control were reviewed in 2015 by Gebreslasie [48] [43,71,72,74,75,80,88], and cyanobacterias [28,81,82,123,137,138,148,150,155] were the most studied. Other studied diseases or pathogens included meningitis [225]; brucellosis [70]; C. imicola [67]; avian pathogens [25,134,136,50]; V. vulnifucus [52]; V. parahaemoliticus [52]; Fasciola hepatica [36]; hand, foot, and mouth disease [20]; Helminth infections (not limited to schistosomiasis) [120,85,21,22]; Lyme disease [108,45,79,110]; Guinea worm [30]; Nipah virus [133]; onchocerciasis [68]; opistorchiasis [146]; rotavirus [69]; typhoid fever [32]; Rift Valley fever [139,125,84]; Murray Valley encephalitis virus …”
Section: Insights From the Literature Reviewmentioning
confidence: 99%
“…GNSSs have been used often in the field of communicable diseases too, including person-to-person transmissible varieties [253,255], vector-borne diseases [21,48,38,252,258,260,257,264,256,95,263], and zoonoses [262,260,254,261,25]. In our search, the most studied communicable disease was malaria.…”
Section: Insights From the Literature Reviewmentioning
confidence: 99%